DEVELOPING RESPONSIBLE APP APPLICATIONS BASED ON E-LEARNING TO SUPPORT ONLINE LEARNING IN ELEMENTARY SCHOOLS - Iin Mutiah K; Muhammad Yunus; Jaja Jamaluddin (Teaching English as a Foreign Language Overseas Journal, 2022)
The aims of this study to develop a Responsible App Based on E-Learning as an Online Learning Support for teachers and students in elementary schools. This type of research is development research which refers to the research procedure proposed by Borg & Gall starting from the information gathering stage to the final product revision in the form of the Responsible App application. The research sample was teachers and students, a total of 51 people. The product development procedure begins with preliminary studies, planning, initial product development, validation, revision, limited trials, operational product revisions, operational trials to final product revisions. The data collection techniques used in this study were observations, interviews, questionnaires, and documentation techniques which were analyzed with percentage data analysis and criteria for validity, practicality and product effectiveness. The results showed that the development of the Responsible App application based on E-Learning can be used as Online Learning Support for students in elementary schools based on the validation result of 1.00 on very valid criteria. The results of the practicality test and product effectiveness test, respectively, have a percentage of 91.23% and 93.60% on the very practical and very effective criteria. Thus, it can be concluded that the development of the Responsible App application is appropriate to be used as a support for students' online learning in elementary schools. The results showed that the development of the Responsible App application based on E-Learning can be used as Online Learning Support for students in elementary schools based on the validation result of 1.00 on very valid criteria. The results of the practicality test and product effectiveness test, respectively, have a percentage of 91.23% and 93.60% on the very practical and very effective criteria. Thus, it can be concluded that the development of the Responsible App application is appropriate to be used as a support for students' online learning in elementary schools. The results showed that the development of the Responsible App application based on E-Learning can be used as Online Learning Support for students in elementary schools based on the validation result of 1.00 on very valid criteria. The results of the practicality test and product effectiveness test, respectively, have a percentage of 91.23% and 93.60% on the very practical and very effective criteria. Thus, it can be concluded that the development of the Responsible App application is appropriate to be used as a support for students' online learning in elementary schools. 23% and 93.60% on the very practical and very effective criteria. Thus, it can be concluded that the development of the Responsible App application is appropriate to be used as a support for students' online learning in elementary schools. 23% and 93.60% on the very practical and very effective criteria. Thus, it can be concluded that the development of the Responsible App application is appropriate to be used as a support for students' online learning in elementary schools.